MOLECULAR INVESTIGATION OF HEMOTROPIC MYCOPLASMAS IN HUMAN BEINGS, DOGS AND HORSES IN A RURAL SETTLEMENT IN SOUTHERN BRAZIL - Rafael Felipe da Costa VIEIRA; Odilon VIDOTTO; Thállitha Samih Wischral Jayme VIEIRA; Ana Márcia Sá GUIMARAES; Andrea Pires dos SANTOS; Naíla Cannes NASCIMENTO; Nelson Jesse Rodrigues dos SANTOS; Thiago Fernandes MARTINS; Marcelo Bahia LABRUNA; Mary MARCONDES; Alexander Welker BIONDO; Joanne Belle MESSICK (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
SUMMARY The aims of this study were to determine the prevalence of hemoplasmas in a rural Brazilian settlement's population of human beings, their dogs and horses, highly exposed to tick bites; to identify the tick species parasitizing dogs and horses, and analyze factors associated with their infection. Blood samples from 132 dogs, 16 horses and 100 humans were screened using a pan-hemoplasma SYBR green real-time PCR assay followed by a species-specific TaqMan real-time PCR. A total of 59/132 (44.7%) dog samples were positive for hemoplasmas (21 Mycoplasma haemocanisalone, 12 ' Candidatus Mycoplasma haematoparvum' alone and 21 both). Only 1/100 (1.0%) human sample was positive by qPCR SYBR green, with no successful amplification of 16S rRNA or 23 rRNA genes despite multiple attempts. All horse samples were negative. Dogs >1 year of age were more likely to be positive for hemoplasmas ( p= 0.0014). In conclusion, although canine hemoplasma infection was highly prevalent, cross-species hemoplasma transmission was not observed, and therefore may not frequently occur despite overexposure of agents and vectors.